DEVELOPMENT OF TECHNICAL SPECIFICATIONS FOR THE MECHANISM OF THE TRADING SYSTEM - et al., Rahimova Sevara (International Journal of Advanced Science and Technology, 2019)
The article described the Unified National Marketplace will be the only mechanism for the sale of domestically produced goods throughout the world through online access, and organizing online receipt of multicurrency payments, thus facilitating the costs associated with organizing trade in goods locally and abroad. One of the main points is the organization of receiving multi-currency payment and simplifying the difficulties associated with the export of products manufactured in the Republic of Uzbekistan, will also allow businesses and individuals to provide their goods to personal stores.There are several types of electronic trading platforms - for commercial customers, for placing government orders. The sites on which electronic transactions are performed by commercial customers are divided into specialized and multi-profile. Users, participants of the sites, held auctions and trades themselves can decide on which of the sites it is more convenient and profitable to work with. In addition, on a multiprofile resource the customer can act as a supplier, the seller - this is dependent on the scope of his activities, on the possibilities.